RELATIONSHIP BETWEEN STUDENT DIFFERENTIAL AND INTEGRAL CALCULUS LEARNING OUTCOMES TO STUDENT DIFFERENTIAL EQUATIONS LEARNING OUTCOMES - R. H. Yanti Silitonga (Universitas Sembilanbelas November Kolaka, 2023)
Differential calculus and integral calculus courses are the foundations of mathematics that are important in understanding and applying differential equations. Students can take the Differential Equation course on condition that they have graduated from the Differential Calculus and Integral Calculus courses. This study aims to determine the relationship between the understanding of differential and integral calculus with students' learning outcomes of differential equations. The population in this study were all 2020 Pattimura University Teaching and Teacher Training Faculty Mathematics Education students who had taken differential calculus, integral calculus, and differential equations courses with a total sample of 33 people. The research method used is quantitative research with correlational methods. This study uses multiple regression analysis which has the aim of finding the form and influence between the independent variables and the dependent variable. Data analysis technique using multiple regression test. Based on the results of the data analysis, it was concluded that there was a significant contribution between learning outcomes of differential calculus on learning outcomes of differential equations seen in the relative contribution of learning outcomes of differential calculus on learning outcomes of differential equations based on the calculation results obtained 56.45% while the relative contribution of learning outcomes of integral calculus 43 .54% of the learning outcomes of differential equations. So it shows that there is a big influence between learning outcomes of differential calculus and integral calculus on learning outcomes of differential equation.